The impact of financial crisis on the performance of commercial banks in a developing economy : empirical evidence from Indonesia. - Sufian, Fadzlan; Habibullah, Muzafar Shah (2010)
The paper seeks to examine the determinants of indonesian banks profitability during the period 1990-2005. The empirical findings suggest that income diversification and capitalization are positively related to bank profitability, while size and cost have negative impacts. During the period under study, credit risk and network embeddedness are not economically significantly related to the profitability of indonesian banks. The impact of economic growth is positive during the crisis and post-crisis periods. We find that the crisis period has negative impact on indonesian banks profitability, while indonesian banks have been relatively more profitable during the post-crisis compared to the pre and crisis periods.